EFEKTIVITAS PENCEGAHAN KORUPSI DI INDONESIA PERSPEKTIF SISTEM HUKUM LAWRENCE M FRIEDMAN - Chandra, Jessica; Kusuma, Rangga; Beliuk, Lintang (JIL : Journal of Indonesian Law, 2025)
This study aims to analyze the effectiveness of corruption prevention in Indonesia from the perspective of the Lawrence M. Friedman legal system, with a focus on strengthening the legal culture through early anti-corruption education and the role of students. The problem of the research departs from the fact that even though Indonesia has various anti-corruption regulations and institutions, corrupt practices still occur, which shows the ineffectiveness of the legal system in carrying out preventive functions. This indicates that the elements of the legal system have not worked in a balanced manner, especially in the aspect of legal culture. This research uses a normative juridical method with a qualitative descriptive approach, through literature studies of laws and regulations, legal literature, reports of anti-corruption institutions, and supporting data such as anti-corruption perception and behavior indexes. The results of the study show that the structure and substance of the law in corruption prevention in Indonesia are relatively available, but not supported by a strong legal culture. The weak internalization of integrity values and legal awareness of the community is the main factor in the low effectiveness of corruption prevention. Therefore, anti-corruption education from an early age and the active role of students as agents of change are important strategies in strengthening the legal culture and encouraging sustainable corruption prevention.